Public Security, Criminal Justice, and Reforming the Security Sector : Security and Justice Thematic Paper - Guehenno, Jean-Marie (Washington, DC: World Bank, 2012)
Discusses prioritization of governance, the rule of law, and security sector reform (SSR). A policy framework identifies the specific characteristics of post-conflict operations, with emphasis on the need to rebuild trust between the state and its people. Demobilization, disarmament, and reintegration (DDR) programs provide an effective transition strategy, but when their main thrust is to create civilian jobs, results have usually been disappointing.The security sector reform (SSR) supplies support needed for the success of DDR programs, because the legitimacy of a reformed security sector means that the security forces reflect the whole country and contributes to building confidence.The implications for the rule of law and criminal justice point to the need for transparent processes, including quasi-judiciary mechanisms, such as truth and reconciliation commissions.Examples are drawn from Haiti and the Democratic Republic of Congo (DRC), where SSR efforts have been extensive and are ongoing, as well as from Afghanistan, Bosnia, East Timor, Rwanda, Sudan, Liberia, and Sierra Leone.